2007
DOI: 10.1364/oe.15.013266
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser written surface waveguides fabricated in Nd:YAG ceramics

Abstract: Near surface channel waveguides have been fabricated in Neodymium doped YAG ceramics by using IR femtosecond laser irradiation at the low frequency regime. Single mode guidance has been demonstrated with propagation losses of ~1 dB/cm. Time resolved confocal micro-luminescence experiments have been used to determine the spectroscopic properties of the Nd(3+) laser ions in the channel waveguide as well as to elucidate the waveguide formation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 18 publications
3
37
0
Order By: Relevance
“…This value has been found to be higher than that reported for a femtosecond written depressed cladding waveguide laser formed in Nd:YAG crystals ͑0.3 dB/ cm͒, 11 but comparable to that found in femtosecond laser written surface channel waveguides fabricated in Nd:YAG ceramics ͑1 dB/ cm͒. 9 According to expression ͑1͒, the laser slope efficiency of our waveguide laser can be even improved by using longer pump wavelengths, since they would lead to a significant reduction in the quantum defect between pump and laser photons which, in turn, will be accompanied by a reduction in the pump induced thermal loading and, therefore, in the undesirable thermal effects. 17 The near field TM 00 mode intensity distribution was measured with a charge coupled device camera.…”
Section: -supporting
confidence: 53%
See 1 more Smart Citation
“…This value has been found to be higher than that reported for a femtosecond written depressed cladding waveguide laser formed in Nd:YAG crystals ͑0.3 dB/ cm͒, 11 but comparable to that found in femtosecond laser written surface channel waveguides fabricated in Nd:YAG ceramics ͑1 dB/ cm͒. 9 According to expression ͑1͒, the laser slope efficiency of our waveguide laser can be even improved by using longer pump wavelengths, since they would lead to a significant reduction in the quantum defect between pump and laser photons which, in turn, will be accompanied by a reduction in the pump induced thermal loading and, therefore, in the undesirable thermal effects. 17 The near field TM 00 mode intensity distribution was measured with a charge coupled device camera.…”
Section: -supporting
confidence: 53%
“…8 Recently, authors reported on the fabrication of near surface channel waveguides in Nd:YAG ceramics. 9 Nevertheless, up to date no attempt has been made, to the best of our knowledge, for the fabrication of buried channel waveguides in Nd:YAG ceramics by femtosecond DLW. The possible application of such waveguides as reliable and integrated laser sources is, therefore, still unexplored.…”
mentioning
confidence: 99%
“…The stress field around waveguides recorded by the femtosecond direct laser writing inside Nd-doped yttrium aluminium garnet (YAG) can be engineered to exert compressive and tensile stresses on the order of ±1 kbar, respectively (up to +5 kbar for compression). Such photomodification can create the following: (i) waveguiding regions due to augmented refractive index Δn = ((n 2 − 1)(n 2 + 2)/2n)(P/E), here P is the pressure and E is the Young modulus, and, (ii) the spectral properties of Nd transitions can be effectively modified via pressure [21,22]. The combined effects of refractive index and emission changes can be utilized for the creation of efficiently lasing waveguide laser-written in Nd:YAG ceramics [23].…”
Section: Stress Confinementmentioning
confidence: 99%
“…Femtosecond laser machining has enabled the manufacture of a wide variety of integrated, threedimensional, multi-functional devices all on a single substrate [1][2][3][4][5][6][7][8][9][10][11][12]. While the benefits of this technology are many, there are still significant technological obstacles that must be overcome to reliably and predictably produce these devices.…”
Section: Introductionmentioning
confidence: 99%